The standard elements for Muslim friendly accommodation premises / Siti Syahirah Saffinee … [et al.] - Saffinee, Siti Syahirah; Has-Yun Hashim, Khairusy Syakirin; Mahamod, Lukman Hakim; Jamaludin, Mohd Aizat; Muflih, Betania Kartika; Othman, Rashidi (Academy of Contemporary Islamic Studies (ACIS), 2017)
Muslim-friendly hotels are targeted to provide shariah complaint and comfortable rooms especially for the Muslim guests. This is in line with the encouragement of good hospitality in Islam. However, even though there are nearly 3000 hotels in Malaysia, only less than 10% are considered as Muslim friendly. Therefore, this study investigates the elements that constitute a Muslim-friendly hotel. Based on the discovered elements, this study proposes a standard and comprehensive Muslim-friendly hotel audit checklist which is significant as a guidance for players of the industry as well as the relevant authorities such as the government, municipals, religious authority including the certification bodies. The checklist is important to avoid the misconspetion among the consumers.